(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
This study aims to identify characteristics of groundwater in Bir Al-Ashhab municipality to determine its suitability for human consumption based on the Water Quality Index (WQI). Groundwater samples in different positions were collected directly from the wells for chemically analyzed in terms of (PH), (TDS), (EC), (TH) and (CL), and WQI was calculated based on these parameters. Geographical Information systems (GIS) were used to produce spatial variation map of groundwater quality in the study area. The results showed that the concentrations of all parameters were higher than permissible limits except the values of (PH). Moreover the values ​​of the water quality index ranged from (125) to (169), which indicates that the groundwater quality in the study area is poor. The spatial distribution maps have indicated that the best groundwater quality is concentrated in north part of the study, and the quality decreases gradually in the southward and direction